2001
DOI: 10.1159/000050182
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Follow-Up Programs in the Reduction of Mortality of Rectal Cancer Recurrences

Abstract: Aim: The aim of this study is to investigate whether patients, who have undergone curative surgery for rectal cancer and present with recurrence of the disease, could have a better chance of radical reoperation and increased survival if they were diagnosed earlier due to a screening program, when they were still asymptomatic, than those who were not followed up and their recurrence is discovered by its symptoms. Methods: 113 patients, 52 men and 61 women (mean age 64.19 years, SD 10.76), who presented recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, Ohlsson et al [30]reported no statistical difference in the survival between patients with or without intensive postoperative follow-up after curative surgery for colorectal carcinoma. Komborozos et al [31]also showed no statistical difference in the survival after treatment of recurrence between patients with or without symptoms. In this study, curative resection rate was 58.7% in patients with asymptomatic local recurrence and 38.2% in patients with symptomatic local recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ohlsson et al [30]reported no statistical difference in the survival between patients with or without intensive postoperative follow-up after curative surgery for colorectal carcinoma. Komborozos et al [31]also showed no statistical difference in the survival after treatment of recurrence between patients with or without symptoms. In this study, curative resection rate was 58.7% in patients with asymptomatic local recurrence and 38.2% in patients with symptomatic local recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption was based on the fact that the intensive strategy increased the proportion of resectable tumor recurrences in the whole series as well as in some subsets of patients; more importantly, it increased the probability of overall survival in patients with stage II lesions or rectal tumors [7]. In contrast, Komborozos et al could not reveal a difference in neither the rate of R0-resection rate for recurrent disease nor the overall rate of survival after surgical treatment of recurrence [29]. …”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies concerning follow-up after resection for colorectal cancer have been published, but most of them are non-randomized single cohort studies, and only a few are prospective randomized studies (7,16,18,25,26,94) or comparative cohort studies (11,15,17,24,91,93) (Table 3). The control groups in all the cohort studies are patients that partly or totally have refused to participate in the follow-up programme.…”
Section: Follow-up Studiesmentioning
confidence: 99%